Open Abdomen A Comprehensive Practical Manual (Hot Topics in Acute Care Surgery and Trauma,, 2018)
This book is the first available practical manual on the open abdomen. The handy format will allow practicing physicians, surgeons, anesthesiologists, nurses, and physiotherapists to use it as a ready source of information on all aspects of management of the open abdomen in a wide variety of settings. The coverage includes, for example, the open abdomen in trauma, intra-abdominal sepsis, and acute pancreatitis, step-by-step descriptions of different techniques with the aid of high-quality color figures, guidance on potential complications and their management, and features of management in different age groups. Throughout, the guidance provided is state of the art, reflecting recent innovations and drawing upon a thorough and up-to-date literature review. Useful tips and tricks are highlighted, and the book is designed to aid in daily decision making. The authors include worldwide opinion leaders in the field, guaranteeing the high scientific value of the content.